Seasonal Variation in the Biological Traits of Invasive Amazon Sailfin Catfish (Pterygoplichthys pardalis) in East Kolkata Wetlands, India - HUSSAN, AJMAL; NAIK, AT RAMACHANDRA; ADHIKARI, SUBHENDU; DAS, ARABINDA; HOQUE, FARHANA; SUNDARAY, JITENDRA KUMAR (Journal of the Indian Society of Coastal Agricultural Research, 2024)
Invading sailfin catfish Pterygoplichthys spp. in East Kolkata Wetlands (EKW), India were studied for their length-weight relationship (LWR), condition factor and reproductive characteristics covering pre-monsoon, monsoon and post-monsoon seasons. Using seine nets, fish samples were taken every month from May to December 2022 from five distinct EKW sites. Season-specific b-values for the LWR showed negative allometric growth, ranging from 2.663 to 2.809. Seasonal variation was negligible for Fulton's condition factor (Kc), which varied between 0.741 and 0.756. The mean relative condition factor (Kn) was likewise found to be near 1 in all seasons (0.999 - 1.041). The sex ratio (male to female) showed an average mean value of 1: 3.61, with no noticeable seasonal change. However, gonado-somatic index (GSI) of males (0.164±0.007) and females (7.174±0.225) during the monsoon months (July - September) was found to be considerably greater (p